Anatomy and Functional Morphology of the Mysticete Rorqual Whale Larynx: Phonation Positions of the U‐Fold - DAMIEN, JULIETTE; Adam, Olivier; Cazau, Dorian; WHITE, Paul; LAITMAN, JEFFREY; REIDENBERG, JOY (The Anatomical Record, 2019)
International audience Many Mysticetes (baleen whales) are acoustically active marine mammals. This is epitomized by rorquals, and specifically male humpback whales (Megaptera novaeangliae) whose complex songs comprise a wide range of vocalizations. The sound production mechanism of odontocetes (toothed whales, including dolphins and porpoises) is well described, in contrast to that of mysticetes whose vocalization mechanism remains a subject of active scientific investigation. Anatomical observations and acoustic signal processing have led to divergent hypotheses under the framework of a production-based approach. We attempt to unify these hypotheses by broadening existing data with our new anatomical investigation, interpreted in light of known acoustical properties of mysticete vocalizations. We examined 15 specimens of four rorqual species: sei whale (Baleanoptera borealis), fin whale (Baleanoptera physalus), minke whale (Baleanoptera acutorostrata), and humpback whale (Megaptera novaeangliae). Based on these data and on previous literature, we propose a description of three functional positions (rest, breathing, and recirculation), unidirectional egressive airflow for sound production (from lungs to laryngeal sac), and new nomenclature for different parts of the U-fold (distal section, midsection, and corniculate flaps). Each of these sections has specific morphological and acoustical properties that support the concept of “mode variation” in baleen whale vocalizations.